2018
DOI: 10.3892/br.2018.1103
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the apoptotic pathway by oxidative stress in spontaneous preterm birth: Single nucleotide polymorphisms, maternal lifestyle factors and health status

Abstract: Abstract. The purpose of the present study was to search for associations between spontaneous preterm birth (sPTB), single nucleotide polymorphisms (SNPs) associated with the apoptotic pathway as triggered by oxidative stress, maternal lifestyle and health status. SNP genotyping [rs7560 for c-Jun N-terminal kinase (JNK), rs9517320 for mammalian STE20-like protein kinase 3 (MST3), rs1049216 for caspase 3 (CASP3)] in the placenta and maternal blood of 300 controls with at-term birth and 43 cases of sPTB was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Tabacova et al (1998) identified elevated cord blood methemoglobin levels and a higher prevalence of preterm birth among a small sample of women exposed to nitrate during pregnancy. Apoptosis (cell death) induced by hypoxia and oxidative stress has been found to confer risk of spontaneous preterm birth (Tarquini et al 2018). Thus, the prooxidant properties of nitrate are a potential mechanistic explanation for the observed association between nitrate and spontaneous preterm birth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tabacova et al (1998) identified elevated cord blood methemoglobin levels and a higher prevalence of preterm birth among a small sample of women exposed to nitrate during pregnancy. Apoptosis (cell death) induced by hypoxia and oxidative stress has been found to confer risk of spontaneous preterm birth (Tarquini et al 2018). Thus, the prooxidant properties of nitrate are a potential mechanistic explanation for the observed association between nitrate and spontaneous preterm birth.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress in pregnancy is one of the posited mechanisms for spontaneous preterm birth (Tarquini et al 2018;Aung et al 2019). Despite its prooxidant properties, very few studies have investigated links between gestational nitrate exposure and preterm birth.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress, characterized by the generation of ROS, is an integral factor in the inflammatory process 35 . Recent studies have demonstrated that oxidative stress plays an important role in infection-induced apoptosis and in the pathogenesis of preterm labor 36 , 37 . LPS triggers inflammatory responses in human gestational tissues by increasing pro-inflammatory cytokines and phospholipid metabolites mediated by activation of the NF-κB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress, characterized by the generation of ROS, is an integral factor in the in ammatory process 29 . Recent studies have demonstrated that oxidative stress plays an important role in infectioninduced apoptosis and in the pathogenesis of preterm labor 30,31 . LPS triggers in ammatory responses in human gestational tissues by increasing pro-in ammatory cytokines and phospholipid metabolites mediated by activation of the NF-κB pathway.…”
Section: Discussionmentioning
confidence: 99%